Status sócio econômico e deficiência intelectual em escolares - Campana, A. de Pádua; Nóbrega, F. J. de; Moraes, S.; Yida, M. (My University, 1977)
Raven's Progressive Matrices were completed by 536 school children. Wechsler's Intelligence Scale for Children was applied to children who performed badly on Raven's Test (percentile 5 or less). Father's occupation and education, items of property and sums of spending money were assessed in all families. Clinical history and physical examination were recorded for deficient children. Mental deficiency was present in 94 children (17.5%); it was more frequent in those from lower socioeconomic classes (90 deficient children in a total of 427); it was more frequent in the peripheral school (69 deficient children) than in the midtown school (relatively less poor children); no significant difference was found in sex distribution among social classes. 67 children had an intelligence quotient between 50 and 69. Undernourishment was severe marked (18 children), moderate (48 children) or absent (26 children). Most children (67) were insufficiently stimulated by their parents.
Socioeconomic status and mental deficiency in school children
Keywords: child; epidemiology; major clinical study; mental deficiency; socioeconomics